2021
DOI: 10.1016/j.rbmo.2020.08.032
|View full text |Cite
|
Sign up to set email alerts
|

Same-sex male couples and single men having children using assisted reproductive technology: a quantitative analysis

Abstract: Same-sex male couples and single men accessing assisted reproductive technology (ART) in Canada report a positive experience. Social support of men who pursued ART and worked with multiple egg donors significantly affected overall experience. Understanding the experiences of unique groups using ART can result in informed, inclusive reproductive healthcare practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…A significant increase in the use of gestational surrogacy in Canada over recent years has also been suggested by studies conducted with both Canadian and international intended gay fathers ( Carone et al. , 2017a , 2017b ; Fantus, 2020 , 2021 ; Fantus and Newman, 2019 ; Hemalal et al. , 2021 ).…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…A significant increase in the use of gestational surrogacy in Canada over recent years has also been suggested by studies conducted with both Canadian and international intended gay fathers ( Carone et al. , 2017a , 2017b ; Fantus, 2020 , 2021 ; Fantus and Newman, 2019 ; Hemalal et al. , 2021 ).…”
Section: Introductionmentioning
confidence: 85%
“…Outside of the current circumstances of the COVID-19 pandemic, intended gay fathers already experience significant challenges in building a family ( Berkowitz, 2020 ; Blake et al. , 2017 ; Hemalal et al. , 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The increase in same-sex male couples accessing (domestic) surrogacy can be linked to changing social attitudes about same-sex marriage and same-sex male couples starting families (Golombok et al, 2018;Hemalal et al, 2021;Lindheim et al, 2019;Norton et al, 2013). There may also be an increased awareness of the ability to undertake a surrogacy arrangement in the UK rather than having to go overseas, driven by campaigns for law reform and an increased visibility of both surrogacy and same-sex parenting in more recent years.…”
Section: Discussionmentioning
confidence: 99%
“…While IVF was traditionally employed to treat heterosexual infertile couples, there has been increasing use by samesex male couples in light of marriage equality and such demand is likely to continue (Blake et al, 2016). Same-sex male couples (and indeed single men or women, who may or may not be gay), while still facing some sociocultural obstacles to becoming families, have been shown to have similar drivers to pursue (biological) parenthood as heterosexual couples who want families (Carone et al, 2017;Hemalal et al, 2021;Smietana, 2018) and there has been a significant increase in the numbers of same-sex male couples pursuing parenthood via assisted reproduction and surrogacy (Dar et al, 2015;Golombok et al, 2018;Perkins et al, 2016). Recent studies have also shown that many transgender men and women have strong desires to become parents, but also that uptake of fertility preservation is low, particularly in transgender men (Alpern et al, 2022;Amir et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Infertile patients require assisted reproductive techniques (ART) such as artificial insemination (AI), in vitro fertilization (IVF), and intracytoplasmic sperm injection (ICSI) to achieve pregnancy [ 14 , 15 ]. Additionally, the use of ART is steadily increasing [ 16 ] given that same-sex couples [ 17 , 18 , 19 , 20 , 21 ], persons who desire to create single-parent families [ 18 , 21 , 22 , 23 ], and individuals who undergo fertility preservation for both medical and nonmedical reasons [ 24 , 25 , 26 ] also benefit from them to ultimately accomplish parenthood.…”
Section: Introductionmentioning
confidence: 99%